Dental anxiety – a joint interest for dentists and psychologists. (28th March 2013) - Carlsson, Sven G.; Wide Boman, Ulla; Lundgren, Jesper; Hakeberg, Magnus
Abstract : This introductory article to the Symposium on Behavioral and Community Dentistry aims to describe the development of research and clinical work on dental anxiety, and includes a discussion of the historical background and the evolution since the 1970s. In view of its pioneering activities in this regard, special focus is placed on research and development at the Institute of Odontology of the University of Gothenburg, Sweden.